2021
DOI: 10.3390/ma14102690
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Study of Fracture Behavior of Rock-Like Material Specimens with Single Pre-Set Joint under Dynamic Loading

Abstract: The Split Hopkinson Pressure Bar (SHPB) is an apparatus for testing the dynamic stress-strain response of the cement mortar specimen with pre-set joints at different angles to explore the influence of joint attitudes of underground rock engineering on the failure characteristics of rock mass structure. The nuclear magnetic resonance (NMR) has also been used to measure the pore distribution and internal cracks of the specimen before and after the testing. In combination with numerical analysis, the paper system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…The dynamic failure modes of the CJRMs in this paper are consistent with similar past studies about physical and numerical simulation tests on the dynamic loading of rock mass [42,46,[75][76][77], which concluded that the failure mode of rock mass under dynamic loading is mainly tensile failure and the compressive shear failure of the CJRMs may be determined by the special properties of basalt columns at low angles. Pan et al [76] studied the dynamic loading of jointed rock mass, and the results show that rock mass with a dip angle of 45-60 is more prone to failure, which is consistent with the thesis in this research that the CJRMs with a dip angle of 60 is the most prone to failure. In addition, cracks in jointed rock mass mainly develop along the joints and are dynamic [77], which is a good mirror of the crack propagation pattern studied in this paper.…”
Section: Discussionsupporting
confidence: 91%
“…The dynamic failure modes of the CJRMs in this paper are consistent with similar past studies about physical and numerical simulation tests on the dynamic loading of rock mass [42,46,[75][76][77], which concluded that the failure mode of rock mass under dynamic loading is mainly tensile failure and the compressive shear failure of the CJRMs may be determined by the special properties of basalt columns at low angles. Pan et al [76] studied the dynamic loading of jointed rock mass, and the results show that rock mass with a dip angle of 45-60 is more prone to failure, which is consistent with the thesis in this research that the CJRMs with a dip angle of 60 is the most prone to failure. In addition, cracks in jointed rock mass mainly develop along the joints and are dynamic [77], which is a good mirror of the crack propagation pattern studied in this paper.…”
Section: Discussionsupporting
confidence: 91%
“…Liu [21] considered that the energy time density and incident energy show an upward trend. Following a further study by Pan [22], it was demonstrated that energy absorption reaches its highest level when the joint angle is 45 • . Li [23] found that the penetration rate of a joint can lead to the increase of energy time density.…”
Section: Introductionmentioning
confidence: 93%
“…The place with a large opening becomes the dominant seepage channel, while for some gas-sealed areas; the seepage diameter is more complicated. Some exploration shows that although some cracks are below the underground water level, they are still dry or have only a small amount of crack water seepage, which shows the unsaturated state of the rock mass [12,13]. The inhomogeneity of seepage is mainly reflected in the different permeability coefficients at different positions in the rock mass space system.…”
Section: Introductionmentioning
confidence: 99%